Characterization of Archaea membrane lipids in radioactive springs using shotgun lipidomics - Řezanka, Pavel; Řezanka, Michal; Kyselová, Lucie; Řezanka, Tomáš (Folia microbiologica, 2025)
Lipids from microorganisms, and especially lipids from Archaea, are used as taxonomic markers. Unfortunately, knowledge is very limited due to the uncultivability of most Archaea, which greatly reduces the importance of the diversity of lipids and their ecological role. One possible solution is to use lipidomic analysis. Six radioactive sources were investigated, two of which are surface (Wettinquelle and Radonka) and four deep from the Svornost mine (Agricola, Behounek, C1, and Curie). A total of 15 core lipids and 82 intact polar lipids were identified from the membranes of microorganisms in six radioactive springs. Using shotgun lipidomics, typical Archaea lipids were identified in spring water, namely dialkyl glycerol tetraethers, archaeol, hydroxyarchaeol and dihydroxyarchaeol. Diverse groups of polar heads were formed in archaeal IPLs, whose polar heads are formed mainly by hexose, deoxyhexose, and phosphoglycerol. The analysis was performed using shotgun lipidomics and the structure of all molecular species was confirmed by tandem mass spectrometry. After acid hydrolysis, a mixture of polar compounds was obtained from the polar head. Further analysis by GC-MS confirmed that the carbohydrates were glucose and rhamnose. Analysis by HPLC-MS of diastereoisomers of 2-(polyhydroxyalkyl)-3-(O-tolylthiocarbamoyl)thiazolidine-4(R)-carboxylates revealed that both L-rhamnose and D-glucose are present in spring samples only in varying amounts. The glycoside composition depends on the type of spring, that is, Wettinquelle and Radonka springs are basically shallow groundwater, while the samples from the Svornost mine are deep groundwater and do not contain glycosides with rhamnose. This method enables quick screening for characteristic Archaea lipids, allowing decisions on whether to pursue further analyses, such as metagenomic analysis, to directly confirm the presence of Archaea.
Keywords: Hot Springs; tandemová hmotnostní spektrometrie; d-glucose; Gas Chromatography-Mass Spectrometry; Radioactive springs; l-rhamnose; Membrane Lipids; Lipidomics; Tandem Mass Spectrometry; Glycerol dialkyl glycerol tetraethers; membránové lipidy; lipidomika; Archaea; Intact polar lipids; plynová chromatografie s hmotnostně spektrometrickou detekcí; horké prameny